COOPERATION NETWORKS: THE CONTRASSENSE OF MICRO AND SMALL COMPANIES IN BAHIA OF ATTACHING HIGH IMPORTANCE BUT NOT PARTICIPATING IN THESE NETWORKS - Hastenreiter Filho, Horacio Nelson; Tellechea, Justina (Revista Valore, 2023)
Interorganizational cooperation, supported by public policy instruments in developed countries, is present in Brazil in localized cases with unquestionably favourable results, such as the successful Network Cooperation Program, coordinated by the state government of Rio Grande do Sul. However, in other regions of the country, there is a difficulty in ensuring the active participation of actors in collaborative processes, regardless of the high importance they attach to this participation. In this article, the possibility of stimulating the competitiveness of micro and small companies was evaluated by fostering the formation and development of cooperation networks. The survey results show that despite the low participation of these companies in cooperative actions, it is recognized that cooperation positively affects business competitiveness. In addition, it was found that the presence of Support Organizations to mobilize, create and oversee the rules applied to the cooperative process is seen as relevant and desired by most companies.